The Jak/STAT pathway: a focus on pain in rheumatoid arthritis - Simon, LS; Taylor, PC; Choy, EH; Sebba, A; Quebe, A; Knopp, KL; Porreca, F (Elsevier, 2020)
Pain is a manifestation of rheumatoid arthritis (RA) that is mediated by inflammatory and non-inflammatory mechanisms and negatively affects quality of life. Recent findings from a Phase 3 clinical trial showed that patients with RA who were treated with a Janus kinase 1 (Jak1) and Janus kinase 2 (Jak2) inhibitor achieved significantly greater improvements in pain than those treated with a tumor necrosis factor blocker; both treatments resulted in similar changes in standard clinical measures and markers of inflammation. These findings suggest that Jak1 and Jak2 inhibition may relieve pain in RA caused by inflammatory and non-inflammatory mechanisms and are consistent with the overarching involvement of the Jak-signal transducer and activator of transcription (Jak/STAT) pathway in mediating the action, expression, and regulation of a multitude of pro- and anti-inflammatory cytokines. In this review, we provide an overview of pain in RA, the underlying importance of cytokines regulated directly or indirectly by the Jak/STAT pathway, and therapeutic targeting of the Jak/STAT pathway in RA. As highlighted herein, multiple cytokines directly or indirectly regulated by the Jak/STAT pathway play important roles in mediating various mechanisms underlying pain in RA. Having a better understanding of these mechanisms may help clinicians make treatment decisions that optimize the control of inflammation and pain.